PROFILING THE VOCABULARY OF NEWS TEXTS AS CAPACITY BUILDING FOR LANGUAGE TEACHERS - Astika, Gusti (Indonesian Journal of Applied Linguistics, 2015)
Abstract: The importance of vocabulary in reading has been discussed extensively in the literature. Researchers claim that vocabulary is essential and has a central role in comprehension.   Development in ICT and easy access to information from the internet necessitate language teachers to have relevant knowledge and skills to utilize pedagogical tools to use authentic online materials for learning purposes.  One of such a tool is the Vocabulary Profiler that can be used to categorize lexical words in a text into different frequency levels: high, low, and academic word list. This paper discusses how to use the Vocabulary Profiler to classify words in a text into the different categories.  The utilization of this tool can significantly alleviate the workload of teachers in selecting vocabulary in  reading text which is conventionally based on teachers’ intuition and perception. The sample text in this paper was selected from VOA website which may not be found in the textbooks currently used at schools. The paper ends with some implication for teaching about vocabulary selection.